3,3′-Dibromo-1,1′-[(propane-1,3-diyldioxy)bis(nitrilomethylidyne)]dibenzene - Dong, Wen-Kui (International Union of Crystallography, 2008)
The molecule of the title compound, C(17)H(16)Br(2)N(2)O(2), lies on a twofold axis that passes through the middle atom of the three-atom trimethylene unit. The two aromatic rings are aligned at an angle of 76.02 (4)°.